Ngalokat Menuju Refleksi Diri - Neng Wina Resky Agustina; Ign. Herry Subiantoro; Ismet Ruchimat (Pascasarjana ISBI Bandung, 2022)
“Lokat Mala” is a contemporary dance work inspired by the rumpaka mamaos of the Cianjuran song entitled “Lokat Mala”. The atmosphere of harmonizing songs stirs the soul, gives longing for a cool, peaceful, and serene rural atmosphere. Lokat Mala leads to a process of self-cleaning when humans try to reflect on the balance of the relationship between God, humans and Nature. Stuart Hall's representation theory is used to interpret mamaos Lokat Mala as content ideas which explain, translate, and express ideas including meaning, language, culture, concepts, reality and imagination. The method of creation or creative process applies the concept of Alma Hawkins covering exploration, improvisation and formation. Jaqueline Smith's construction method used in constructing sensitivity includes auditory stimulation, visual stimulation, kinesthetic stimulation, tactile stimulation and idea stimulation. The embodiment of religious ideas and experiences about self-memory, represented in the form of a dance structure as a symbol of harmony and balance in outward and spiritual life. The choreography combines self-reflection, self-motivation, and self-strength.Keywords: Dance, Lokat Mala, Reflection of life, Representation